Congenital syphilis as the cause of multiple bone fractures in a young infant case report - Maria Koliou; Elpida Chatzicharalampous; Myria Charalambous; Kyriakos Aristeidou (BMC, 2022)
Abstract Background The differential diagnosis of multiple unexplained bone fractures in a young infant usually includes child abuse or bone disease such as osteogenesis imperfecta. Bone abnormalities can occur in 60-80% of cases with congenital syphilis and may be the sole manifestation. However, this frequent manifestation of this rare disease such as congenital syphilis is frequently disregarded. We describe a case of a young infant with multiple long bone fractures diagnosed with congenital syphilis. Case presentation This 2-month-old male patient was referred to our hospital because of fractures of the ulna and distal radius bilaterally and noisy breathing with the suspicion of osteogenesis imperfecta. After thorough examination, the infant had anemia and a palpable spleen. We performed a screen for congenital infections among other investigations, which revealed positive non-treponemal and treponemal antibodies for syphilis. Hence the diagnosis for Congenital Syphilis was made. We performed a lumbar puncture (LP) which showed mild pleocytosis. The patient was treated with intravenous aqueous penicillin G 200 000 UI/KG per day for 10 days. In addition, a single dose of intramuscular penicillin G benzathine 50 000 UI/KG was given due to the abnormal result of CSF. On follow up admission 6 months later, the new syphilis serology had much improved and the new LP revealed no abnormal findings. Conclusions We present this case report in order to remind of a common manifestation of congenital syphilis, a rare disease which needs to be included in the differential diagnosis of multiple unexplained fractures in early infancy. In our case the fractures were symmetric and bilateral and they were accompanied by anemia and mild hepatosplenomegaly which led to the investigation of congenital syphilis as a possible cause. However, two thirds of infants with congenital syphilis are asymptomatic at birth. All women should have a proper syphilis screening during pregnancy.